ANALISIS FRASA ENDOSENTRIK KOORDINATIF DAN FRASA ENDOSENTRIK APOSITIF DALAM NOVEL JAIS DARGA NAMAKU KARYA AHDA IMRAN KAJIAN SINTAKSIS - Bakir Hasyim Bakir Hasyim; Ali Manshur Ali Manshur (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The context of this study is an analysis of coordinate and apositive endocentric phrases in the novel Jais Darga Namaku by Ahda Imran. Phrases are not only found in scientific or non-fiction works but also in works of fiction or literary works such as in short stories and novels. Among them is a novel by Ahda Imran entitled Jais Darga Namaku. The novel Jais Darga Namaku tells the story of the life journey of an Indonesian woman with all her ambitions. That ambition made her known as Jais Darga or Madam Darga, an international art dealer in Paris. It was this ambition that kept Jais wandering to many distant lands, that he could no longer tell whether he was